Human Amniotic Fluid: a New Challenge for the Control of Seborrheic Dermatitis - Mohadeseh Nasiri; Leila Fozouni (Pasteur Institute of Iran, 2020)
Introduction: Seborrheic dermatitis is a skin condition that has become widespread in the recent decades. This study aimed to investigate the antimicrobial effect of amniotic fluid of pregnant women on the growth of ketoconazole-resistant Malassezia species isolated from patients with seborrheic dermatitis. Methods: We obtained human amniotic fluid from 20 pregnant women during amniocentesis and cesarean delivery at hospitals of Gonbad-e Kavus, northeastern Iran. Malassezia isolates were collected from 120 patients suspected of seborrheic dermatitis and were identified using species-specific biochemical tests. Antibiotic susceptibility and minimum inhibitory concentration (MIC) of Malassezia isolates against ketoconazole were determined by the broth microdilution method. Also, the antifungal effect of various concentrations of amniotic fluid on ketoconazole-resistant Malassezia isolates was assayed using the disk diffusion method. Results:  The mean MIC of ketoconazole against Malassezia isolates was 0.3 μg/mL, with the most changes observed at 0.5 μg and 1 μg/mL. Ketoconazole  inhibited the growth of Malassezia isolates completely, at a concentration of 8 μg/mL. Moreover, amniotic fluid showed inhibitory effects on 60% of ketoconazole-resistant Malassezia furfur isolates and 45% of Malassezia globosa isolates. There was a significant correlation between amniotic fluid concentration and the diameter of the growth inhibition zone (P<0.01). Conclusion: Our findings indicated that amniotic fluid could exhibit favorable dose-dependent antifungal activity against ketoconazole-resistant Malassezia isolates from patients with seborrheic dermatitis. Further studies are required to confirm the efficiency of amniotic fluid for the treatment of such infections.